Antimicrobial photodynamic therapy and dental plaque: A systematic review of the literature - Santin, G. C.; Oliveira, D. S.B.; Galo, R. [UNESP]; Borsatto, M. C.; Corona, S. A.M. (Hindawi, 2014)
Background. The aim of this study was to perform a systematic review of the literature on the efficacy of antimicrobial photodynamic therapy (PDTa) on cariogenic dental biofilm. Types of Studies Reviewed. Studies in vivo, in vitro, and in situ were included. Articles that did not address PDTa, those that did not involve cariogenic biofilm, those that used microorganisms in the plankton phase, and reviews were excluded. Data extraction and quality assessments were performed independently by two raters using a scale. Results. Two hundred forty articles were retrieved; only seventeen of them met the eligibility criteria and were analyzed in the present review. Considerable variability was found regarding the methodologies and application protocols for antimicrobial PDTa. Two articles reported unfavorable results. Practical Implications. The present systematic review does not allow drawing any concrete conclusions regarding the efficacy of antimicrobial PDTa, although this method seems to be a promising option.